Recent Catalytic Applications of Ferrocene and Ferrocenium Cations in the Syntheses of Organic Compounds - Eike B. Bauer (Molecules)
Ferrocene and its oxidized counterpart, the ferrocenium cation, represent a fascinating class of organometallic compounds with broad utility across various fields, including organic synthesis, pharmaceuticals, and materials science. Over the years, ferrocene, ferrocenium cations, and their derivatives have also gained prominence for their versatility in catalytic processes. This review article offers an overview of the research of the last decade into ferrocene- and ferrocenium-based catalysis. Key developments are highlighted in catalytic oxidation, cross-coupling, polymerization reactions, and redox-switchable catalysis, as well as the application of ferrocenium cations as Lewis acid catalysts.